Implementasi Pelayanan Samsat Tanjak dalam Meningkatkan Pelayanan Pajak Kepada Masyarakat Perawang - Yanti, Varizka; Magriasti, Lince (Jurnal Administrasi Pemerintahan Desa, 2024)
This study was conducted to discuss the implementation of SAMSAT TANJAK services to the people of Tualang sub-district, Siak district. This research was structured using a quasi-qualitative or quasi-qualitative type of research. The method that the author uses in this research is the simple research design (SRD) method. Theresults of this research are the implementation of Samsat Tanjak services in improvingtax services to the Perawang community. The findings in this research show that fromthe aspect of information system support, company location, atmosphere of the serviceplace/ decoration and layout have not run optimally, while from the management aspect, customer handling and company equipment have run well.